Selenate-enriched urea granules are a highly effective fertilizer for selenium biofortification of paddy rice grain - Premarathna, Lakmalie; McLaughlin, Mike J.; Kirby, Jason K.; Hettiarachchi, Ganga M.; Stacey, Samuel; Chittleborough, David J. (My University, 2013)
We examined the effects of applied selenium (Se) species, time of application, method of application and soil water management regime on accumulation of Se in rice plants. Plants were grown to maturity in a temperature- and humidity-controlled growth chamber using three water management methods: field capacity (FC), submerged until harvest, and submerged and drained two weeks before harvest; two Se species: selenate (SeO[subscript 4] ˉ²) and selenite (SeO[subscript 3]ˉ²) applied at a rate equivalent to 30 g haˉ¹; and four application methods: i) Se applied at soil preparation, ii) Se-enriched urea granules applied to floodwater at heading iii) foliar Se applied at heading and iv) fluid fertilizer Se applied to soil or floodwater at heading. Total Se concentrations in rice grains, husks, leaves, culms and roots were measured, as well as Se speciation in grains from the Se-enriched urea granule treatment. Highest Se concentrations in the grain occurred with SeO[subscript 4] ˉ² and with fertilizer applied at heading stage; SeO[subscript 4]ˉ²-enriched urea granules applied at heading increased grain Se concentrations 5 to 6 fold (by 450-600 μg kgˉ¹) compared to the control (no fertilizer Se applied) in all water treatments. Under paddy conditions other Se fertilization strategies were much less effective. Drainage before harvesting caused Se to accumulate in/on rice roots, possibly through adsorption onto iron plaque on roots. Rice grains contained Se mainly in the organic form as selenomethionine (SeM) which comprised over 90 % of the total grain Se in treatments fertilized with SeO[subscript 4]ˉ² -enriched urea granules. The results of this study clearly show of the fertilizer strategies tested that biofortification of Se in rice grains can best be achieved in lowland rice by broadcast application of SeO[subscript 4]ˉ² -enriched urea granules to floodwater at heading stage.
Citation: Premarathna, Lakmalie, Mike J. McLaughlin, Jason K. Kirby, Ganga M. Hettiarachchi, Samuel Stacey, and David J. Chittleborough. “Selenate-Enriched Urea Granules Are a Highly Effective Fertilizer for Selenium Biofortification of Paddy Rice Grain.” Journal of Agricultural and Food Chemistry 60, no. 23 (June 13, 2012): 6037–44. https://doi.org/10.1021/jf3005788.
Keywords: Selenium; Selenite; Selenate; Biofortification; Fertilizer; Rice; Se enriched urea